Kamikaze diaries : reflections of Japanese student soldiers - Ohnuki-Tierney, Emiko (University of Chicago Press, 2006)
"We tried to live with 120 percent intensity, rather than waiting for death. We read and read, trying to understand why we had to die in our early twenties. We felt the clock ticking away towards our death, every sound of the clock shortening our lives." So wrote Irokawa Daikichi, one of the many kamikaze pilots, or tokkotai, who faced almost certain death in the futile military operations conducted by Japan at the end of World War II. This moving history presents diaries and correspondence left by members of the tokkotai and other Japanese student soldiers who.